2016
DOI: 10.4236/ojpm.2016.61005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dry Eye and Its Association with Various Risk Factors in Rural Setup of Western Uttar Pradesh in a Tertiary Care Hospital

Abstract: Purpose: To study the prevalence of dry eye in a hospital based population of rural setup and to evaluate its association with various risk factors. Material and Methods: In this cross sectional study, patients above 20 years of age were screened randomly for dry eye. An 8 points questionnaires, slit lamp examination of meibomian glands, tear film breakup time, fluorescein staining of cornea, schirmer test were used to diagnose dry eye. The diagnosis was made when three of the five parameters were positive. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The prevalence of DED is more in females as compared to males. Relationship between prevalence of DED with respect to age was reported very recently by Ranjan et al, 2016 15 . This increase may be due to association between hormonal status and pre and postmenopausal period Our study suggests that hormones may influence the prevalence of DED in pre and post menopausal women.…”
Section: Mean Values Of Fbs Ppbs and Hba1c By Sex And Its Associatiomentioning
confidence: 82%
“…The prevalence of DED is more in females as compared to males. Relationship between prevalence of DED with respect to age was reported very recently by Ranjan et al, 2016 15 . This increase may be due to association between hormonal status and pre and postmenopausal period Our study suggests that hormones may influence the prevalence of DED in pre and post menopausal women.…”
Section: Mean Values Of Fbs Ppbs and Hba1c By Sex And Its Associatiomentioning
confidence: 82%
“…Prevalence of dry eye disease varies from country to country and ranges between 5% to 35% in different age groups. [16][17][18][19] Approximately 25-30 million people are affected. The prevalence of DED in India is higher than the global prevalence and ranges from 18.5% to 54.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In another three-year study involving cleanroom workers, the TBUT and McMonnies questionnaire results worsened with more years of employment [23]. In a tertiary hospital-based study in rural India, ten participants were factory workers, and nine were found to have DED, but the type of the factory was not reported [44]. A pilot study carried out on 78 workers in a chemical factory has found that the TBUT for workers exposed to plastic and paint intermediates (6 ± 4.84 s) were significantly (p < 0.012) lower than non-exposed workers (11 ± 4.80 s).…”
Section: Previous Studiesmentioning
confidence: 98%